LGG-54. Asthma reduces glioma formation by T cell decorin-mediated inhibition of microglia. (3rd June 2022) - Chatterjee, Jit; Sanapala, Shilpa; Cobb, Olivia; Bewley, Alice; Cordell, Elizabeth; Garbow, Joel; Holtzman, Michael; Gutmann, David
Abstract: To elucidate the mechanisms underlying the reduced incidence of brain tumors in children with Neurofibromatosis type 1 (NF1) and asthma, we leverage optic pathway glioma ( Nf1 -OPG) mice, human and mouse RNAseq data, and two different experimental asthma models. Following ovalbumin or house dust mite asthma induction at 4-6 weeks of age (WOA), Nf1 -OPG mouse optic nerve volumes and proliferation are decreased at 12 and 24 WOA, indicating no tumor development. This inhibition is accompanied by reduced expression of the microglia-produced optic glioma mitogen, Ccl5. Human and murine T cell transcriptome analyses reveal that inhibition of microglia Ccl5 production results from increased T cell expression of decorin, which blocks Ccl4-mediated microglia Ccl5 expression through reduced microglia NFκB signaling. Decorin or NFkB inhibitor treatment of Nf1 -OPG mice at 4-6 WOA inhibits tumor formation at 12 WOA, thus establishing a potential mechanistic etiology for the attenuated glioma incidence observed in children with asthma.